Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar Mata Pelajaran Fiqih : Studi Kasus Siswa Kelas XI MIPA MA Mambaul Hisan Badalpandean Ngadiluwih Kediri - Johansah, Mochamad Abraham (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
One of the most essential aspects of the teaching and learning process is the employment of the appropriate learning model, because the learning model may be utilized as a determining factor in the success of attaining the goals set forth in the teaching and learning process in schools. As a result, the teacher must master a variety of learning models, including the contextual teaching and learning learning model, that are tailored to the subject matter to be taught. The correct learning model can make the teaching and learning process go more smoothly, and students” learning achievement will rise as a result. In light of this, the researchers devised the following problem formulations. (1) How does MA Mambaul Hisan Ngadiluwih Kediri use the contextual teaching and learning learning approach to Fiqh subjects? (2) Does MA Mambaul Hisan Ngadiluwih Kediri’s contextual teaching and learning methodology effect the learning outcomes of Figh subjects? (3) how are learning outcomes for fiqh subjects evaluated at MA Mambaul Hisan Ngadiluwih Kediri? This study employs both qualitative and quantitative methods and is referred to as a mixed method study. Test results data, participant observation, in-depth interviews,and documentation are all examples of data gathering approaches. Researchers employed four methods for data analysis, including (1) descriptive statistics, (2) inductive methods, (3) deductive methods, (4) comparison methods. The following are the findings of this study: (1) The learning outcomes of class XI MIPA MA mambaul hisan ngadiluwih kediri in fiqh subjects were classified as appropriate using the Contextual Teaching and Learning learning model. The phases in the implementation of CTL employing 7 (seven) learning components, namely: Contructivism, asking, finding, study groups, Modeling, Reflection, and actual evaluation, have been relatively maximal, and it has been executed effectively. (2) There is an influence on student learning outcomes when  the contextual teaching and learning learning paradigm is used, as indicated by the test result in each cycle: according to the findings, the mean pre-test score of 72,72 is lower than the first post-test score of 75,52. The average post-test 2 score is 80,69, is also less than the third post-test score 84,45, (3) The evaluation of learning outcomes for Fiqh MA Mambaul hisan Ngadiluwih Kediri subjects has been fairly effective, as evidenced by the question response orally between the teachers and students during the learning process. Keywords: Contextual Teaching and Learning, Fiqh Subjects, Learnig Outcomes.